Frequency, Risk Factors and Antibiotic Sensitivity Pattern of Extended-Spectrum Beta-Lactamase Producing Escherichia coli and Klebsiella pneumoniae Causing Urinary Tract Infection: Experience from a Tertiary Care Hospital of Bangladesh (BIRDEM Medical Journal, 2017)
Background: Urinary tract infection (UTI) due to extended-spectrum beta-lactamase (ESBL) producing organisms are increasing. This study was designed to evaluate the frequency of ESBL-positive Escherichia coli and Klebsiella pneumoniae causing UTI, their antibiotic sensitivity pattern and possible risk factors.Methods: This case-control study was done in BIRDEM General Hospital, Dhaka, Bangladesh from January to March 2016. Patients with UTI due to ESBL-positive E. coli and K. pneumoniae were cases and non-ESBL organisms were controls.Results: Total 98 patients with UTI due to E. coli (84) and K. pneumoniae (14) were eligible for analysis. Twothirds of E. coli (56/84, 66.7%) and two-fifths of K. pneumoniae (6/14, 42.9%) were ESBL-positive (cases, 62) and rest 36 patients were controls (UTI due to non-ESBL E. coli or K. pneumoniae). There was no significant difference in relation to age (p=0.757), sex (p=0.548), presence (p=0.696), duration (p=0.050) or control of diabetes (p=0.448) between cases and controls. Regarding risk factors responsible for UTI due to ESBLpositive organisms, long duration (?5 years) of diabetes was significant (OR=6.87, 95% CI=2.34-20.16, p=0.0004). On multivariate logistic regression, presence (p=0.002) and long duration of diabetes (p=0.002), past history of UTI (p=0.004) and history of hospitalization due to UTI (p=0.005) appeared as significant risk factors for UTI due to ESBL-positive E. coli or K. pneumoniae. Imipenem, amikacin, gentamycin and nitrofurantoin were among the most sensitive antibiotics.Conclusion: Almost two-thirds of the UTI cases were due to ESBL-positive organisms in this study. Imipenem, aminoglycosides and nitrofurantoin were among the most sensitive antibiotics. Long duration of diabetes, past history of UTI and hospitalization due to UTI were significant risk factors for ESBL-positivity.Birdem Med J 2017; 7(2): 155-159